When Does Prosocial Motivation Deliver? A Dual-Motivations Approach to Social Enterprise Outcomes - Au, Kevin; Jeong, Sophia Soyoung; Hsu, Anna J. C.; Xiao, Yingzhao (Journal of business ethics, 2024)
Scholars and leaders have assumed that prosocial motivation is the primary driver for social enterprises (SEs) to do good. Despite the significance of prosocial motivation, we argue that it may not be the single driver for SE motivation. A dual-motivations approach based on insights from motivation research is proposed to examine how different types of SE motivation can act together to influence the outcomes of SEs. Empirical findings based on survey data from Hong Kong demonstrate that dual motivations—prosocial-intrinsic and prosocial-extrinsic motivations—explain the outcomes of SEs beyond what the direct effects of prosocial motivation can explain separately. Based on moderation analyses, intrinsic motivation enhances the positive relationships between prosocial motivation and business and social outcomes, whereas extrinsic motivation undermines the relationship related to business outcomes. Implications for research on social entrepreneurship and business ethics are discussed.